Analysis of the Influence of Production, International Prices, and Exchange Rates on Coffee Export Volume in Indonesia in 2002-2022 - Erna Wati; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to examine the effect of production, international prices and exchange rates on the volume of coffee exports in Indonesia in 2002-2022. This research is a quantitative research. The data source is obtained from the Central Bureau of Statistics. Testing using multiple linear regression analysis. The results showed that coffee production, the international price of coffee and the rupiah exchange rate could explain the 2002-2022 coffee export volume of 31.3%. The partial test results show that coffee production and the rupiah exchange rate have no effect on the volume of coffee exports. And the international price of coffee has a positive effect on the volume of coffee exports. Meanwhile, the results of simultaneous tests show that coffee production, international coffee prices and the rupiah exchange rate together have no effect on the volume of coffee exports from 2002-2022.